Optimizing the Clinical Pathway for Acute Orofacial Trauma: A Comprehensive Evaluation of Prehospital Handoff, Emergency Assessment, Diagnostic Imaging, Rapid Laboratory Testing, Pharmacological Management, Rehabilitation Referral, and Health‑Record C - Alkhathlan, Khalid Turky; Alghamdi, Ahmed Alkordi; Alotaibi, Saleh Nashat; Alrowaily, Badr Awadh; Alqahtani, Turki Rathwan Saad; Saeed Alqahtani, Waleed Mansour; Alabdulsalam, Abdullah Mohammad; Shammary, Faiz Ahmed Al; Alhassan, Abdulmohsin Abdulaziz; Almatrafi, Jamal Osaymir; Salem Mesfer Salem Alqahtani; Al-Qahtani, Mubarak Mohammed; et al. (International Journal of Aquatic Research and Environmental Studies, 2025)
Acute orofacial trauma presents a unique constellation of diagnostic and management challenges that span prehospital care, emergency department (ED) triage, diagnostic imaging, laboratory evaluation, pharmacologic management, and onward rehabilitation and documentation. Delays or breakdowns at any step can prolong time-to-definitive care and worsen functional, aesthetic, and psychosocial outcomes. This article synthesizes current evidence and best practices to propose an optimized, integrated clinical pathway for acute orofacial trauma. Drawing on literature from orofacial pain and dental trauma, emergency imaging, analgesic practice, prehospital handoff research, care-pathway studies, and documentation quality improvement, we review (1) prehospital priorities and handoff models that improve ED readiness, (2) ED assessment and triage algorithms that balance airway/bleeding control with dental preservation, (3) targeted diagnostic imaging and rapid point-of-care testing strategies, (4) evidence-based multimodal analgesia and antimicrobial/anti-inflammatory pharmacotherapy for acute dental and orofacial injuries, (5) criteria and timing for early allied-health rehabilitation referral, and (6) essential components of health-record continuity and trauma documentation. We identify operational enablers (standardized handoff templates, imaging algorithms, analgesic bundles, and trauma documentation proformas) and barriers (ED crowding, variable documentation, interprofessional knowledge gaps). Finally, we propose measurable process and outcome metrics for implementation and research, and offer a pragmatic pathway intended to reduce time-to-definitive care and improve patient-centered outcomes.
Keywords: orofacial trauma, prehospital handoff, emergency assessment, diagnostic imaging, analgesia, documentation, rehabilitation, clinical pathway